RBL-PHP: Simulation of Lean Construction and Information Technologies for Prefabrication Housing Production - Li, X.; Shen, G.; Wu, Peng; Fan, H.; Wu, H.; Teng, Y. (ASCE, 2018)
Prefabrication housing production (PHP) is widely promoted due to its potential benefits, such as reduced construction time and improved quality. However, PHP also faces many uncertainties and constraints due to the highly fragmented process of managing design, construction, and supply chain. Lean construction principles and information technologies, e.g., radio frequency identification (RFID) and building information modeling (BIM), have proven to be effective in helping to reduce the uncertainties and remove the constraints in PHP. However, the availability of appropriate training or pedagogical approaches to transfer and share the lean knowledge and information techniques has impeded their adoption. To address the issue, this study develops a hands-on learning tool, which is an advanced simulation game called RBL-PHP [i.e., RFID/BIM/lean (RBL)-PHP]. The RBL-PHP simulates the process of PHP from manufacturing and logistics to the on-site assembly by integrating an RFID-enabled BIM platform with lean construction into training students and practitioners. Four workshops are conducted at Hong Kong Polytechnic University, Hong Kong, China, to assess the participants' learning experience by using ex-ante and ex-post surveys. In each workshop, the performance of PHP is tested separately in a traditional round and a RBL-enabled round on indicators including the percentage of plan complete (PPC), extra cost, and the productivity index. The results indicate that the stability and efficiency of PHP are improved in the RBL-enabled round. In addition, the simulation game can significantly improve the understanding of various knowledge concepts in PHP, such as prefabrication production structure, standardized work, smart construction objects, information sharing and communication, and real-time tracking and visualization, when compared with a traditional computer-based multimedia presentation approach. It can be adopted as a useful platform to effectively train practitioners in the PHP sector on the use of lean, BIM, and other innovative information technologies.